EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN MEDIA VISUALISASI 3D UNTUK MENINGKATKAN KETERAMPILAN TRANSLASI SATU LEVEL REPRESENTASI SISWA PADA MATERI ASAM BASA - Rifki Nur Hidayati; Lisa Tania; Andrian Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effectiveness of discovery learning assisted by 3D visualization media in improving students' single-level translation ability of chemical representation on acid-base topics. The population consisted of all eleventh-grade students of SMA Negeri 1 Gedong Tataan, Pesawaran Regency, in the 2026/2027 academic year. The sample was selected using a cluster random sampling technique, with Class XI.2 as the experimental class and Class XI.1 as the control class. The experimental class received discovery learning assisted by 3D visualization media (PhET and ConnChem), while the control class received discovery learning only. This study used a quasi-experimental method with a pretest-posttest control group design. Data were analyzed using an independent sample t-test with SPSS version 30.0. The results showed that the average n-gain of the experimental class was 0.53 (high category), significantly higher than the control class average of 0.48 (medium category), with a significance value (2-tailed) of 0.041 (p < 0.05) and an effect size of 0.92 (large category). Thus, discovery learning assisted by 3D visualization media is effective in improving students' single-level translation ability of chemical representation on acid-base topics